EVALUATION OF THE STRUCTURE OF CAMPUS II OF MUHAMMADIYAH UNIVERSITY, WEST SUMATERA WITH NON-LINEAR STATIC PUSHOVER - Saputra, Romi Sani; RM, Redha Arima; Masrilayanti, Masrilayanti (JURNAL DARMA AGUNG, 2023)
Abstract The campus building II of the Muhammadiyah University of West Sumatra is one of the facilities used for the Faculty of Engineering lectures that must be considered both in terms of safety and comfort in the planning process. Being in an earthquake-prone location, the campus II building of the Muhammadiyah University of West Sumatra became the object of this research. All forms of regulations related to building safety have been issued by the government, this is to ensure the quality, both quality and quantity of the building. The purpose of this study was to evaluate the performance of the campus II building of the Muhammadiyah University of West Sumatra from the influence of earthquake forces both from the x direction and from the y direction, then how the collapse pattern occurred. This research was conducted using ETABS V.16.2.1 software to model the building under study and to calculate the performance based design based on the regulations of the Applied Technology Council (ATC-40), FEMA 356 and FEMA 440. The results showed that the shear force obtained from the thrust given in the X-direction was 43.561.8104 kN at Step 8 the displacement value was 317.320 mm and the thrust given in the Y-direction was 39274.5448 kN at Step 11 the value displacement is 289,851 mm. Displacement in the building does not exceed the allowable displacement, so that the building is safe against the design earthquake. The maximum total drift is 0.013 and the maximum In-elastic drift is 0.011, so the building is included in the Damage Control (DO) performance level.